2010
DOI: 10.4009/jsdt.43.309
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of upper-gastrointestinal complication after taking cinacalcet hydrochloride

Abstract: Key words:cinacalcet hydrochloride, activity of gastric acid secretion, gastric emptying, gastrointestinal motility, medicine releasing acetylcholine 〈Abstract〉 After taking cinacalcet hydrochloride, hemodialysis patients with secondary hyperparathyroidism often complain of upper gastrointestinal symptoms. In order to evaluate gastrointestinal function, the activity of gastric acid secretion was examined by measuring intragastric pH, serum gastrin and serum pepsinogen concentration and gastric emptying test wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The main adverse effects associated with cinacalcet are GI events, such as nausea, vomiting, and abdominal discomforts [ 18 ]. It has also been reported that cinacalcet inhibited gastric emptying in hemodialysis patients who developed GI events following its treatment [ 21 ]. Cancer chemotherapeutic agents are known to cause GI symptoms and have been shown to induce delayed gastric emptying in humans, similar to cinacalcet treatment [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main adverse effects associated with cinacalcet are GI events, such as nausea, vomiting, and abdominal discomforts [ 18 ]. It has also been reported that cinacalcet inhibited gastric emptying in hemodialysis patients who developed GI events following its treatment [ 21 ]. Cancer chemotherapeutic agents are known to cause GI symptoms and have been shown to induce delayed gastric emptying in humans, similar to cinacalcet treatment [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such GI intolerability limits the dose of cinacalcet and may result in poor compliance or discontinuation [ 19 , 20 ]. Given reports of cinacalcet inhibiting gastric emptying in hemodialysis patients [ 21 ], delayed gastric emptying seems to contribute to GI events caused by cinacalcet treatment. We therefore hypothesized that abnormal GI motility might be a mechanism underlying GI events and a good marker of side effects in the GI tract.…”
Section: Introductionmentioning
confidence: 99%
“…Cinacalcet has been shown to promote an increase of blood flow and vascular ectasia under the condition of arterial brittleness [11]. Therefore, administration of this agent might play an important role in causing a renal hemorrhage subsequent to an increase of renal blood flow or vascular ectasia as in our cases.…”
Section: Discussionmentioning
confidence: 87%
“…Cinacalcet has been recently considered to cause digestive symptoms by decreasing GI motility via activating the CaSR in gut, since human antral gastrin cells express the CaSR [ 19 ]. The activation of the CaSR increases serum gastrin level and basal gastric acid secretion in healthy adults [ 20 ], whereas cinacalcet delayed GI motility associated with elevated serum gastrin concentration that was independent of gastric acid secretion in HD patients [ 21 ]. On the other hand, there was no association of antacids and past history of upper GI diseases with the GI adverse events of cinacalcet in the present study ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%